Assessing Knowledge, Attitude and Practice About Oral Cancer Detectionand Treatment Among Dental Undergraduates of Maharashtra, Karnataka and Goa States - Tendulkar, Sneha; Ashwinirani SR, Ashwinirani SR; Hamand, Asmita R.; Suragimath, Girish (Journal of Neonatal Surgery, 2025)
Background: Oral cancer refers to the squamous cell carcinoma, arising from the epithelial cell lining of the oral cavity. It may affect any part of the oral mucosa but usually affects floor of mouth, buccal mucosa, gums, lip and tongue. Oral cancer is associated with consumption of tobacco, alcohol and other factors like HPV virus. Aims and objectives: The present study was aimed to assess the knowledge , attitude and practice about oral cancer among dental undergraduates from states of Maharashtra, Karnataka and Goa. Methodology: A questionnaire study was conducted on 250 dental undergraduates from the states of Maharashtra, Karnataka and Goa through means of Google forms consisting of 15 questions about knowledge ,attitude and practice about oral cancer. The institutional ethical committee clearance was obtained before the start of the study. A set of questions were circulated through whatsapp and the responses were collected and analyzed. Results: Out of 250 participants 74.2% were females and 25.8% were males. Majority of the participiants were between 20-21 years accounting for 49.8%.. Maximum number of student responses were obtained from the state of Maharashtra (76.5%), followed by Karnataka (20.2%) and lastly Goa (3.3%). About 97.7% participants were aware of oral cancer and various forms of smoked and smokeless tobacco. About 61%, claimed of never having participated in Oral Cancer awareness campaigns. Amongst the surveyed students, 97.2% students agreed to oral cancer campaigns being effective. About 93% proportion of dental students agreed upon oral cancer to be treatable. About 91.5% of participants knew that risk of oral cancer increases with age. A total of 97.2% students knew that tobacco and tobacco products aids in progression of oral cancer.Among the total evaluated students, 98.6% agreed on alcohol having a synergistic effect on the progression of oral cancer. A total of 202(94.8%) students identified that a non-healing ulcer is a sign indicative of oral cancer.About 84% of students stated that loss of alveolar bone radiographically and exfoliation of adjacent teeth also is a sign of oral cancer.Among the total surveyed students, 95.8% students believed that proliferative growth in oral cavity of tobacco consumers is indicative of oral cancer.Almost 94.8% of participants were aware of association of viral etiology like HPV- human papilloma virus in oral cancer. About 97.2% students felt that dentists play a major role in detection of oral cancer. Among the total surveyed students, only about 79.8% students were aware of different modalities for oral cancer detection. A large number of dental students, (56.3%), claimed to have never received formal training in detection and screening of oral cancer. Conclusion: Based on the results of our study majority of participants were aware about etiological factors clinical features and treatment modalities of oral cancer.